INCREASING STUDENT LEARNING OUTCOMES IN HYDROCARBON MATERIALS THROUGH THE APPLICATION OF THE PROBING PROMPTING MODEL IN CLASS X MIPA 3 SMA NEGERI 1 BANGSAL MOJOKERTO - Wahyudi (Sean Institute, 2022)
The results of the observations obtained daily test scores of classes with the percentage of completeness only 60%. This shows that the learning outcomes of hydrocarbons in class X MIPA 3 SMA Negeri 1 Bangsal can be categorized as poor. To improve learning outcomes, classroom action research was conducted which consisted of two cycles. Each cycle consists of stages of planning, implementation, observation and reflection. The subjects of this study were students of SMA Negeri 1 Bangsal Class X MIPA 3 academic year 2017/2018 which consisted of 34 students. The data collection instruments were evaluation questions for the cognitive domain which were carried out at the end of each cycle and observation sheets for the affective and psychomotor domains. Based on the results and discussion, it can be concluded that learning using the probing prompting model can provide convenience for teachers in learning, make learning student-centered, complete learning outcomes, and can teach and train students' character behavior. The implementation of the lesson plans was categorized as good with an average score of 3.0 in the first cycle and 3.27 in the second cycle. Student activity reached 85.26% in the first cycle and increased to 92.22%. In the aspect of scientific behavior, both cycles show that they are in the good category. Mastery learning outcomes also showed an increase, from 73.77% in the first cycle to 90% in the second cycle.